Management of Transplant Renal Artery Pseudoaneurysm and Literature Review - Luke Anders; Rachel Stephens; Melissa Laub; Rushay Amarath-Madav; Ahmad Mirza; Muhammad Irfan Saeed (Case Reports in Transplantation)
Renal transplantation is the ultimate treatment for end-stage renal disease patients. However, vascular complications can impact renal allograft outcomes. Extrarenal pseudoaneurysms (EPSA) are a rare complication occurring in 1% of transplant recipients. We report a case series of extrarenal pseudoaneurysm after kidney transplant with different clinical presentations and management strategies. Given the rarity of EPSA, literature describing this complication is limited to single case reports or small retrospective case series. We also provide an up-to-date review of 76 articles on mycotic, bacterial, and idiopathic EPSAs. Allograft removal is considered standard treatment, but new endovascular alternatives may allow allograft salvage. EPSA should be managed with a multidisciplinary approach. Surveillance with renal ultrasound is recommended in patients considered high risk.